Rheological Behavior of the Composites of Carboxymethylcellulose-Zinc Oxide/Starch - Coutinho, Marcio da Silva; da Silva, Danielle Cristina Fernandes; Xavier, Gustavo Ribeiro; Rumjanek, Norma Gouvêa; de Oliveira, Paulo Jansen (Acta Scientiae et Technicae; v. 5 n. 1 (2017), 2018)
The rheological behavior of the carboxymethylcellulose (CMC) / starch blends with and without zinc oxide (ZnO) have been investigated by controlled shear rate testing ramps. All blends showed high shear thinning flow behavior, (n=0,10 - 0,32) without ZnO and (n=0,10-0,29) with ZnO. The consistency index (K) and apparent viscosity (η a,100 ) decreased with increasing amount of starch and with the addition of 1% wt ZnO. The results also showed that occurs an inversion in the elastic and viscous modulii behavior between 25 and 70 0 C, obeying the Arrhenius equation. The study of activation energy showed that ZnO acts in the CMC phase, increase of viscosity of mixtures. The creep and recovery test indicated a decrease in the viscosity zero shear rate, indicating an increase of viscous character.  The phase angle results also confirm an increase of viscosity with addition of ZnO.